Settlement of civil disputes through mediation: its effectiveness and challenge in the District Court - Henny Saida Flora; Andi Hartawati; Sachsyabillah Dwi Maharani Yusuf (Leges Privatae, 2025)
This study aims to examine the effectiveness of mediation in resolving civil disputes and to identify various challenges faced at the District Court of Bandung. The approach used is normative-empirical juridical, combining analysis of the prevailing legal provisions particularly Supreme Court Regulation (PERMA) No. 1 of 2016 with empirical data obtained through interviews, observations, and document studies of civil cases undergoing mediation. The findings indicate that although mediation has been normatively integrated into the civil justice system, its effectiveness remains low. The main obstacles include the public's low legal awareness regarding the benefits of mediation, the limited number and competence of judge-mediators, and the lack of facilities and institutional support. Furthermore, mediation is often perceived merely as an administrative obligation rather than a substantive dispute resolution mechanism. Therefore, regulatory reform, continuous mediator training, and intensive public education are needed to make mediation a more effective, efficient, and equitable alternative for dispute resolution.